A new Cryptalyra species from Colombia (Hymenoptera: Megalyridae) - Shaw, Scott Richard (Zootaxa, 2003)
A new species of Megalyridae, Cryptalyra colombia Shaw, is described. This is the first record of the parasitoid wasp family Megalyridae from Colombia, and only the second known species of the genus Cryptalyra Shaw.